Evaluation of transverse and tensile bond strength of repaired nylon denture base material by heat, cold and visible light cure acrylic resin - Firas A Farhan; Ghazwan A A; Ali A M (College of Dentistry/ University of Baghdad, 2014)
Background: Denture fracture is one of the most common problems encountered by the patients and prosthodontists. The objective of present study was to evaluate the transverse strength of nylon denture base resin repaired by using conventional heat polymerized, autopolymerized and visible light cure VLC resins, surface treatment that used for repair and adjustment of insufficient nylon denture bases and in case of addition of artificial teeth. As these corrective procedures are common chair side procedures in dental clinic. Materials and methods: One hundred twenty nylon specimens were prepared by using metal patterns with dimension of (65x10x2.5 mm) length, width, and thickness respectively for transverse strength test while for tensile bond strength a dumbbell-shaped with measurement (65x12.5x25mm) length, width, and thickness respectively were flasked with stone. The nylon specimens were molded by reflasked with dental stone that used as an index for these specimens in the repair procedure and repaired with 45 degree bevel joint by using metal holding device. The two parts of nylon specimen to be repaired were realigned in its repair index and adhere with special adhesive material to stabilize the combination during repair procedure. The dough of heat and cold cure resin was packed into the joint and then cured. The specimen repaired with cold cure resin was placed in the Ivomat containing water at (40C) and pressure (30IB/inch) for 15 minutes. The specimen repaired with VLC was placed in the light cure unit for 4 minutes following manufacturers instruction. The fractured nylon specimens were divided according to the type of repaired materials into (40) specimens received heat cure acrylic and the (40) specimens received cold cure acrylic and the other 40 specimens received VLCR. Each 40 specimens were subdivided according to the type of surface treatment received into 20 specimens were treated with coarse stone bur (control), 20 specimens were treated with combination of coarse stone bur and monomer of the heat cure acrylic. After that the specimens were subjected to transverse Tr and tensile bond TB strength tests. For each test 10 specimens. Results and conclusions: This study showed that specimens treated with combination of coarse stone bur and monomer of the acrylic (heat, cold or VL cure) had the highest transverse and tensile strength values, followed by the specimens treated with coarse stone bur. The results showed that the specimens repaired with heat cure acrylic had transverse and tensile strength values higher than the specimens repaired with cold and VL cure acrylic when compared between subgroups of heat, cold and VL cure acrylic that received the same treatments.